2017
DOI: 10.1158/1078-0432.ccr-17-1151
|View full text |Cite
|
Sign up to set email alerts
|

MUC1-Mediated Metabolic Alterations Regulate Response to Radiotherapy in Pancreatic Cancer

Abstract: Purpose MUC1, an oncogene overexpressed in multiple solid tumors including pancreatic cancer, reduces overall survival and imparts resistance to radiation and chemotherapies. We previously identified that MUC1 facilitates growth promoting metabolic alterations in pancreatic cancer cells. The present study investigates the role of MUC1-mediated metabolism in radiation resistance of pancreatic cancer by utilizing cell lines and in vivo models. Experimental design We used MUC1 knockdown and overexpressed cell l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…Cancer cells undergo metabolic reprogramming to adapt to the proliferative demands and stressful microenvironments by increasing the uptake of nutrients and their incorporation in the biosynthetic pathways [22,33,34]. The Warburg effect represents metabolic adaptations in proliferating cells and cancer cells where increased glucose uptake, despite the presence of oxygen, sustains anabolic pathways that culminate into biomass production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells undergo metabolic reprogramming to adapt to the proliferative demands and stressful microenvironments by increasing the uptake of nutrients and their incorporation in the biosynthetic pathways [22,33,34]. The Warburg effect represents metabolic adaptations in proliferating cells and cancer cells where increased glucose uptake, despite the presence of oxygen, sustains anabolic pathways that culminate into biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it has been shown that cancer cells reroute glucose and other nutrients into anabolic pathways to provide building blocks essential for cell division [20]. Multiple oncogenes and signaling pathways, beyond Kras and p53, have since been demonstrated to regulate metabolic reprogramming and contribute to poor therapy response [20][21][22][23][24]. As metabolic reprogramming plays a pivotal role in cancer initiation, progression, and therapy responsiveness, different diagnostic techniques based on metabolism are routinely utilized in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of several cancer therapeutics is linked to their effect on metabolic alterations in tumor cells (46). Hence, combining strategies to target metabolism along with the current standard of care will prevent resistance to the therapeutics and may kill the tumor cells more effectively.…”
Section: Introductionmentioning
confidence: 99%
“…These GO terms might be associated with nucleotide metabolism, which was involved in radiotherapy [29] . Refer to MF, "Binding", "protein methyltransferase activity", "histone methyltransferase activity", "histone methyltransferase activity (H3-K4 speci c)" and "histone-lysine N-methyltransferase activity" were highly enriched.…”
Section: Discussionmentioning
confidence: 99%